Zygmunt Grzegorz WĄSOWICZ - DOBRUCKI, Andrzej (Archives of Acoustics, 2014)
Zygmunt G. Wąsowicz, PhD emeritus of the Chair of Acoustics and Multimedia, Wrocław University of Technology, passed away on the 8th of January 2014. His whole professional career was associated with the acoustics.